Pengaruh Kepuasan Kerja dan Dukungan Organisasi yang Dirasakan terhadap Niat untuk Tinggal Dimediasi Komitmen Organisasi : (Studi Kasus di PT.Wangta Agung Surabaya) - Wiwit Lusiana; Siti Mujanah; Achmad Yanu Alif Fianto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Job satisfaction is one thing that triggers the intention to continue working at a company. This research investigates the influence of job satisfaction and perceived organizational support on organizational commitment. Also investigate whether organizational commitment is a good mediator. This study conducted a survey of employees at PT Wangta Agung Surabaya. Using a purposive sampling method with sample criteria being employees who had worked for at least 1 year, 94 respondents were obtained. The data was then analyzed using Structural Equation Modeling. The findings show that job satisfaction and perceived organizational support make a positive contribution to organizational commitment. Research also proves that organizational commitment mediates the relationship between job satisfaction and perceived organizational support on employee intention to stay. This study contributes to understanding employee behavior by using the framework of Organizational Commitment and Intention to Stay in service companies, which can also be applied to other public companies.